Safety and efficacy of benzoic acid as a technological feed additive for weaned piglets and pigs for fattening. (16th January 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The additive under assessment is pure benzoic acid (> 99.8%), manufactured in the form of flakes. It is intended to be used as a technological feed additive (acidity regulator) in feedingstuffs for weaned piglets and pigs for fattening, with maximum contents of 5, 000 and 10, 000 mg/kg complete feed, respectively. Benzoic acid is safe for weaned piglets at 5, 000 mg/kg complete feed, and at 10, 000 mg/kg complete feed for pigs for fattening. The use of benzoic acid in feedingstuffs for piglets and pigs for fattening at the maximum application rate will not affect exposure of consumers to residues or metabolites of concern via food from treated animals. Therefore, the use of benzoic acid as technological additive in feeds for pigs to a maximum inclusion level of 10, 000 mg/kg is considered safe for consumers. Benzoic acid is a skin and eye irritant but is not considered to be a skin sensitiser. Exposure via inhalation is unlikely. The use of benzoic acid in feedingstuffs for piglets and pigs for fattening will not pose a risk for the environment. Benzoic acid is efficacious as an acidity regulator in feedingstuffs for weaned piglets and pigs for fattening.